Effects of biochar and fertilizer management on sunflower (Helianthus annuus L.) feedstock and soil properties. Issue 5 (16th April 2017) - Pfister, Matthew; Saha, Subhrajit
ABSTRACT: The need for bioenergy is increasing with increase in global energy demand, and sustainable soil and fertilizer management practices for bioenergy feedstock production are gaining importance. In this greenhouse study, we evaluated the effects of biochar and fertilizer nitrogen on soil and energy crop sunflower ( Helianthus annuus L. var. Giganteus). Sunflower plants were treated with three rates of biochar, control (0 Mg ha −1 ), low (25 Mg ha −1 ) and high (50 Mg ha −1 ), and three rates of fertilizers, 0% (control), 50% (low) and 100% (high) of the recommended nitrogen dose. Plant height, quality (chlorophyll content), biomass yield, feedstock energy, ash content and tissue nutrients were measured along with soil moisture and pH. Results showed an 11% increase in mean plant height under low biochar compared to control biochar-treated plants. High nitrogen treatment produced 26% and 18% more stalk and total above-ground plant (whole plant) biomass, respectively, compared to the control nitrogen treatment. High biochar treatment resulted in higher soil moisture holding, but lower soil pH than the control biochar treatment. Plant quality, energy and ash contents were not affected by either biochar or nitrogen. The plant tissue analysis provides a complete tissue macro- and micronutrient information on sunflower cultivar Giganteus, which was not done previously.